Mitochondrial ATP synthase activity is impaired by suppressed O-GlcNAcylation in Alzheimer's disease. (10th September 2015) - Cha, Moon-Yong; Cho, Hyun Jin; Kim, Chaeyoung; Jung, Yang Ouk; Kang, Min Jueng; Murray, Melissa E.; Hong, Hyun Seok; Choi, Young-Joo; Choi, Heesun; Kim, Dong Kyu; Choi, Hyunjung; Kim, Jisoo; et al.
Abstract : Glycosylation with O -linked β- N -acetylglucosamine ( O -GlcNAc) is one of the protein glycosylations affecting various intracellular events. However, the role of O -GlcNAcylation in neurodegenerative diseases such as Alzheimer's disease (AD) is poorly understood. Mitochondrial adenosine 5′-triphosphate (ATP) synthase is a multiprotein complex that synthesizes ATP from ADP and Pi . Here, we found that ATP synthase subunit α (ATP5A) was O -GlcNAcylated at Thr432 and ATP5A O -GlcNAcylation was decreased in the brains of AD patients and transgenic mouse model, as well as Aβ-treated cells. Indeed, Aβ bound to ATP synthase directly and reduced the O -GlcNAcylation of ATP5A by inhibition of direct interaction between ATP5A and mitochondrial O -GlcNAc transferase, resulting in decreased ATP production and ATPase activity. Furthermore, treatment of O -GlcNAcase inhibitor rescued the Aβ-induced impairment in ATP production and ATPase activity. These results indicate that Aβ-mediated reduction of ATP synthase activity in AD pathology results from direct binding between Aβ and ATP synthase and inhibition of O -GlcNAcylation of Thr432 residue on ATP5A.